Weight-related behaviors and weight loss maintenance: a cross-sectional study in Cyprus - Yiannis Koutras; S. Chrysostomou; K. Giannakou; M. Yannakoulia (BMC, 2021)
Abstract Background This study examined the differences between maintainers and regainers regarding obesity related eating behaviors. A secondary objective was to develop an eating behavior index predicting the likelihood of successful weight loss maintenance. Methods The current cross-sectional evaluation conducted in Cyprus was part of the MedWeight (Greek) study. Eligible for participation were Cypriot (maintainers = 145; regainers = 87) adult men and women who reported being at least overweight (BMI ≥25 kg/m2) and experienced an intentional weight loss of ≥10% of their maximum lifetime weight, at least 1 year before participation. Among other assessments, weight-related behaviors were evaluated through Weight-Related Behaviors Index (WRBI). Results Statistically significant differences between the two groups were observed regarding meals per day (P = 0.008), frequency of eating home cooked meals (P = 0.004) and WRBI total score (P = 0.022). Results from logistic regression models indicated that the odds of maintaining weight loss increase at 30% (Model 1: P < 0.05, Odds ratio 1.306, 1.095-1.556 95% C.I., Model 2: P < 0.05, OR 1.308, 1.097-1.560 95% C.I.) and at 38% after adjusting for physical activity (Model 3: P < 0.05, OR 1.377, 1.114-1.701 95% C.I..) for each point scored in WRBI total score. Conclusions Eating more frequently home cooked meals and less eating away from home meals may be beneficially associated with weight loss maintenance. WRBI seems to be a useful tool when dealing with patients who have previously lost significant weight.